PRINCIPLES FOR MANAGING TEAM IN CHALLENGING SITUATIONS - Yan yuxin; Tazhieva Samal (Scientific Research and Experimental Development, 2024)
Team management in challenging circumstances calls for adaptability, flexibility, and strategic thinking. Having a clear goal vision is one of the fundamentals. The team must understand that every action is intended to achieve a shared outcome, and the leader must communicate clear tasks and a long-term goal to the group. In difficult situations, there is an even greater need for open communication and candid criticism. It is important for participants to feel free to express their thoughts and inquiries. By doing this, miscommunications are reduced and trust is preserved. The distribution of responsibilities is another crucial factor. Teams need to be able to work independently and solve problems fast in challenging circumstances. In turn, it is the leader’s responsibility to establish an environment where each participant feels valued and supported. Finally, stress resistance and the ability to control emotional reactions are necessary. The leader serves as an example, inspiring the team to remain calm and focused. This management structure allows you to adapt to changes and achieve results even in unstable conditions